Desain Alat Kompaksi Untuk Produksi Glass Cosindo (Coin Sejarah Indonesia) Dengan Material Serbuk Dari Sampah Botol Kaca - Muhamad; Reival Rey Yusti; Arvian Iswahyudi (Politeknik Negeri Jakarta, 2023)
Currently the use of glass material as bottles or beverage packaging is decreasing, but the bottle waste that was used in previous time is still left. This become problems in society. Processing that is usually done by melting glass bottles, but not all can be done with this method. because of this, a new method for processing glass bottle waste deserves to be researched and applied. This study aims to design a tool that can be used for printing glass materials using the compaction method. The compacting tool is designed to print glass powder with a pressure of 5 tons. By making this tool, the variety of glass processing will increase. In addition to glass materials, this tool can also be used to print other materials. This tool will be designed using Solidworks software. The design process begins with manual calculations for construction strength and material selection, then 3D models and 3D assemblies are made. The process ends by simulating the software. The results of the simulation show the strength of the tool construction based on the planning and calculations that have been done.